Buyers’ response to third-party quality certification: Theory and evidence from Ethiopian wheat traders - Abate, Gashaw T.; Bernard, Tanguy; Bulte, Erwin; Miguel, Jérémy Do Nascimento; Sadoulet, Elisabeth (International Food Policy Research Institute, 2024)
When quality attributes of a product are not directly observable, third-party certification (TPC) enables buyers to purchase the quality they are most interested in and reward sellers accordingly. Beyond product characteristics, buyers’ use of TPC services also depends on market conditions. We study the introduction of TPC in typical smallholder-based agriculture value chains of low-income countries, where traders must aggregate products from many small-scale producers before selling in bulk to downstream processors, and where introduction of TPC services has oftentimes failed. We develop a theoretical model identifying how different market conditions affect traders’ choice to purchase quality-certified output from farmers. Using a purposefully designed lab-in-the-field experiment with rural wheat traders in Ethiopia, we find mixed support for the model’s prediction: traders’ willingness to specialize in certified output does increase with the share of certified wheat in the market, and this effect is stronger in larger markets. It, however, does not decrease with the quality of uncertified wheat in the market. We further analyze conditions where traders deviate from the theoretically optimal behavior and discuss implications for future research and public policies seeking to promote TPC in smallholder-based food value-chains.